Reconstructing the Legal Protection of Confiscated Assets in Indonesia's RUPBASAN through a Contextual Islamic Law Perspective - Wahyu Ardianto Machpudj; Aidir Aimin Daud; Andi Muhammad Sofyan; Hotlarisda Girsang; Thresia Hilda Mathelda Yenkase Krey (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The integrity of confiscated assets in Indonesia's criminal justice system is both a constitutional imperative and — from the perspective of Islamic law — a normative obligation rooted in the maqāṣid al-sharī'ah objective of ḥifẓ al-māl (preservation of property). Yet the State Confiscated Goods Storage House (Rumah Penyimpanan Benda Sitaan Negara — RUPBASAN), established under Article 44 of Law No. 8 of 1981 (KUHAP), continues to operate under a fragmented legal framework that lacks enforceable sanctions, adequate infrastructure, and coherent institutional positioning. Despite managing confiscated assets valued at over 17 trillion Rupiah, RUPBASAN's legal protection regime has not been examined through the lens of Islamic criminal law (fiqh al-jinayah) and the principle of amānah (trustworthiness as a legal duty of the state). This study addresses that gap through normative legal research employing statutory, conceptual, and comparative approaches, analyzing RUPBASAN's legal framework against both positive Indonesian law and contextual Islamic legal principles. The findings establish three conclusions: first, Article 44(2) KUHAP prohibits misuse of confiscated objects but provides no criminal sanctions — a normative gap that contravenes both the rule of law and the Islamic principle of lā ḍarar wa lā ḍirār (no harm shall be inflicted); second, the planned transfer of RUPBASAN management to the Attorney General's Office raises unresolved checks and balances concerns that Islamic governance theory (siyāsah shar'iyyah) addresses through the doctrine of institutional separation of taḥqīq (investigation) and qaḍā' (adjudication); and third, a ḥifẓ al-māl-informed reconstruction of RUPBASAN's legal framework — incorporating mandatory sanctions, digital asset tracking, and third-party good-faith protections — offers a contextually legitimate pathway for reform. This study contributes a contextual Islamic law framework for asset protection governance in Indonesia's criminal justice system.